Sustainable Agriculture Development Program in Changing the Mindset of Farmers in Cikurubuk Village - Dinn Wahyudin; Setiadi, Edi; Evan Firdaus (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Cikurubuk Village has invaluable wealth in the form of abundant water springs that are scattered throughout the village area, so that they become a source of life for the people in the Cikurubuk Village area and its surroundings. Based on existing data, Cikurubuk Village has 10 (ten) springs. Gradually farmers are able to change their mindset, so that they do not continue to depend on government subsidised fertilisers which are increasingly difficult to obtain and at high prices by repairing the soil ecosystem that was damaged by the use of synthetic fertilisers and pesticides used over the years. The method used is descriptive analytic, which is a method that focuses on awareness (descriptive) through situations and events that occur in the community related to the object of research, namely the behaviour of the village community when farming organic rice in an effort to local food security. Agricultural cultivation, making Cikurubuk village a role model for other farms that are able to reduce unemployment by producing one superior product developed from the innovation of patani rice from organic agricultural cultivation